2000
DOI: 10.1110/ps.9.11.2218
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal region of cystatin A (stefin A) binds to papain subsequent to the two hairpin loops of the inhibitor. Demonstration of two‐step binding by rapid‐kinetic studies of cystatin A labeled at the N‐terminus with a fluorescent reporter group

Abstract: The three-dimensional structures of cystatins, and other evidence, suggest that the flexible N-terminal region of these inhibitors may bind to target proteinases independent of the two rigid hairpin loops forming the remainder of the inhibitory surface. In an attempt to demonstrate such two-step binding, which could not be identified in previous kinetics studies, we introduced a cysteine residue before the N-terminus of cystatin A and labeled this residue with fluorescent probes. Binding of AANS-and AEDANS-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…A somewhat different mechanism involving a pre-equilibrium complex followed by a reorganization step was suggested for cystatin A binding papain. , The biphasic behavior of cystatin A/papain interaction was observed by following independently the inhibition of the catalytic activity of papain (where a linear dependence of k obs on protein concentration was observed), while the spectroscopic probe (which monitors the accumulation of the native complex) showed a hyperbolic dependence of k obs on protein concentration. This example demonstrates that characterization of the association behavior may depend on the probe used to monitor it.…”
Section: Intermediates Along the Association Pathwaymentioning
confidence: 99%
“…A somewhat different mechanism involving a pre-equilibrium complex followed by a reorganization step was suggested for cystatin A binding papain. , The biphasic behavior of cystatin A/papain interaction was observed by following independently the inhibition of the catalytic activity of papain (where a linear dependence of k obs on protein concentration was observed), while the spectroscopic probe (which monitors the accumulation of the native complex) showed a hyperbolic dependence of k obs on protein concentration. This example demonstrates that characterization of the association behavior may depend on the probe used to monitor it.…”
Section: Intermediates Along the Association Pathwaymentioning
confidence: 99%
“…61,62 This is in contrast to papain and cathepsins L and S, which bind family 1 and 2 cystatins according to a one-step mechanism. [63][64][65][66] Likewise, the present experimental kinetics values, corresponding to the tight-binding inhibition of His110Ala cathepsin B by both kininogens, strongly suggest that the disruption of the salt bridge between His110 and Asp22 results in increased mobility of the occluding loop and a subsequent improved accessibility to the active site as previously discussed in detail by Pavlova et al 36 and Redzynia et al, 35 leading to a single, one-step reaction mechanism similar to that observed for occluding loop-lacking cathepsins interacting with stefins and cystatins. Human stefin B, similarly to kininogens and their isolated inhibitory domains, binds tightly to papain and cathepsin L and more weakly to cathepsin B. Stefin B also has a lower affinity to cathepsin B than ovocystatin or stefin A.…”
Section: His110ala Cathepsin B But Not Wild-type Cathepsin B Forms mentioning
confidence: 99%
“…Insertion of cyclic consensus sequence containing motifs or the replacement of existing amino acids by these cyclic consensus elements in protein α helices or β‐turns should also provide important structural information, provided that the resulting modifications do not impair function. Likewise, the impact of the attachment of these consensus containing elements to the N‐terminus, another region considered accessible and flexible in some proteins (32,34,35), might be another potential region of interest.…”
Section: Discussionmentioning
confidence: 99%